Political Process For Preparation Of Seated Island Regions As A Government Of Sebatik City ( 2006-2012) Nunukan Regency - Febriyandi, Didi (Government Studies of Muhammadiyah Malang University/AIPPTM, 2019)
This paper looks at how the political dynamics that occurred in the Sebatik City expansion process in 2006-2012. The process of regional expansion can be understood as a political phenomenon by involving long administrative and political processes. This paper focuses on looking at political aspects so that it discusses in detail the interests of actors and how these actors articulate their interests. The research method used is descriptive qualitative. Primary data collection techniques are done through observation, structured interviews. For secondary data collection is done by documentation and library techniques.The results showed that the political process is complicated because it involves many interests of political actors making the Sebatik City expansion not realized until now. Although academic studies declared eligible and supported by the majority of Sebatik Island, high-level negotiations-negotiations have failed to realize Sebatik as Daera h Autonomy New (DOB). The political process that occurred did not create a consensus so that there was a conflict of interests that ultimately made the Sebatik City Expansion process hampered. Key Words: decentralization, regional autonomy, outer islands, division